Improving neurosurgical communication and reducing risk and registrar burden using a novel online database referral platform. (3rd March 2016) - Matloob, Samir A.; Hyam, Jonathan A.; Thorne, Lewis; Bradford, Robert
Abstract: Objectives : Documentation of urgent referrals to neurosurgical units and communication with referring hospitals is critical for effective handover and appropriate continuity of care within a tertiary service. Referrals to our neurosurgical unit were audited and we found that the majority of referrals were not documented and this led to more calls to the on-call neurosurgery registrar regarding old referrals. We implemented a new referral system in an attempt to improve documentation of referrals, communication with our referring hospitals and to professionalise the service we offer them.Methods : During a 14-day period, number of bleeps, missed bleeps, calls discussing new referrals and previously processed referrals were recorded. Whether new referrals were appropriately documented and referrers received a written response was also recorded. A commercially provided secure cloud-based data archiving telecommunications and database platform for referrals was subsequently introduced within the Trust and the questionnaire repeated during another 14-day period 1 year after implementation.Results : Missed bleeps per day reduced from 16% (SD ± 6.4%) to 9% (SD ± 4.8%; df = 13, paired t -tests p  = 0.007) and mean calls per day clarifying previous referrals reduced from 10 (SD ± 4) to 5 (SD ± 3.5; df = 13, p  = 0.003). Documentation of new referrals increased from 43% (74/174) to 85% (181/210), and responses to referrals increased from 74% to 98%.Conclusion : The use of a secure cloud-based data archiving telecommunications and database platform significantly increased the documentation of new referrals. This led to fewer missed bleeps and fewer calls about old referrals for the on call registrar. This system of documenting referrals results in improved continuity of care for neurosurgical patients, a significant reduction in risk for Trusts and a more efficient use of Registrar time.